N2-fixation and phosphate solubilization efficiencies, adaptability and related functional genes, in bacterial strains isolated from soils with high contents of Fe - Souza, André Alves de (2022)
One of the great challenges in the recovery process of degraded areas is the supply of nitrogen (N) and phosphorus (P) together with the need to increase the levels of organic matter. In this sense, the use of native grasses in association with phosphate-solubilizing bacteria (BSF) together with the symbiotic association between tree legumes and noduliferous N2-fixing bacteria (BFNN), appears as a good alternative to meet this need. However, the lack of studies with plant species better adapted to the conditions where they will be used in association with native strains, becomes the major obstacle to the expansion of the use of this combination. The objective of this work was to evaluate the efficiency of BFNN and BSF in association with Enterolobium contortisiliquum and Paspalum densum respectively and the prospection of genes of bacteria efficient in BFN and P solubilization. The symbiotic efficiency of BFNN was evaluated in a greenhouse under conditions axenic strains with the inoculation of 39 strains of the genus Bradyrhizobium compared with an efficient strain and controls without inoculation. Subsequently, 12 strains selected among the 39 were evaluated in non-sterile soil from an iron mining area, using the same controls as in the previous test. To evaluate the efficiency of BSF, an in vitro solubilization test was initially performed with 58 strains inoculated in GELP medium containing FePO4, compared with a control without inoculation. Of these 58 strains, nine were selected to carry out a test with soil from a mining area, in association with Paspalum densum and having as controls soluble or insoluble sources of P without inoculation. Four strains were selected based on soil assays for the study of genomic DNA. Assays with BFNN showed that plants inoculated with strains selected for genomic DNA sequencing had high symbiotic efficiency in association with Enterolobium contortisiliquum, evidenced by the good performance in the analyzed variables. Genomic DNA analysis showed the presence of important genes linked to tolerance to high Fe and Mn conditions, such as pin5, acdS, sodA, bfr, gshB and gor genes. The tests with BSF showed a good performance of three of the four strains selected for genomic DNA analysis, among them the UFLA 219 strain of the genus Burkholderia, which had also presented the best performance in the in vitro test. The genomic DNA of the BSF showed the presence of a series of genes linked to the phosphate solubilization mechanism, with emphasis on the genes related to the release of organic acids. In this way, it was demonstrated that the success of the association between growth-promoting bacteria and the inoculated plants depends on genes related to more specific mechanisms in the promotion of growth, but also on genes that confer greater adaptability to the studied strains.